Numerical approximation of the potential in the two-dimesional inverse scattering problem. (10th December 2015) - Barceló, Juan A; Castro, Carlos; Reyes, Juan M
Abstract: We present an iterative algorithm to compute numerical approximations of the potential for the Schrödinger operator from scattering data. Four different types of scattering data are used as follows: fixed energy, fixed incident angle, backscattering and full data. In the case of fixed energy, the algorithm coincides basically with the one recently introduced by Novikov (2015 Sbornik: Math. 206 120–34 ), where some estimates are obtained for large energy scattering data. The numerical results that we present here are consistent with these estimates.